Case Report: Paliperidone Palmitate in the Management of Bipolar I Disorder With Non-compliance - Li, Kanglai; Liao, Yingtao; Yang, Zhihua; Yang, Caishuang; Chen, Minhua; Wu, Xiuhua; Gan, Zhaoyu (Frontiers in Psychiatry, 2021)
Background: Medication non-adherence is prevalent in patients with bipolar disorder (BD). Long-acting injectable antipsychotics (LAIAs) are widely used to improve compliance with treatment. This study aimed to illustrate the effectiveness, compliance and safety profile of once-monthly paliperidone palmitate (PP1M), a novel therapeutic LAIA, in the management of bipolar I disorder ( BDⅠ) Method: A prospective follow-up was arranged to 11 bipolar I disorder (BDⅠ) patients who were prescribed PP1M as monotherapy or adjunctive treatment. Severity of symptoms, disturbing behavior, status of employment, 17-item Hamilton Depression Rating Scale (HAMD-17) and the Young Mania Depression Scale (YMDS) were evaluated at the baseline and the endpoint of follow-up. Clinical Global Impression-Bipolar Disorder-Severity of Illness Scale (CGI-BP) and Treatment Emergent Symptom Scale (TESS) were measured at each injection of PP1M. Compliance, relapse or switch, and new hospitalization were monitored through the period of follow-up. Results: The median duration of treatment was 14 months, ranging from 5 to 22 months. The scores (mean±standard deviation) of HAMD-17, YMDS and CGI-BP generally decreased from the baseline (16.1±10.3, 30.9±12.6, 5.3±0.7) to the endpoint (7.4±5.7, 3.7±3.2, 2.3±0.7). No disturbing behavior was detected at the endpoint. Neither new hospitalization nor manic/mixed episode occurred during treatment, while mild to moderate depressive episodes were reported in 3 cases. The status of employment of 10 participants (90.9%) was improved, and no new safety concern was detected. Conclusion: PP1M might offer a new valid treatment option in the long-term management of BDⅠ, especially for those with poor compliance with oral medication. However, more studies are needed to further justify its such role.